Promoting pro-environmental behaviours at work: The role of green organizational climate and supervisor support - Leitão, P.; Mouro, C.; Duarte, A. P.; Luís, S. (PsyEcology, 2024)
Employees’ pro-environmental behaviours at work can contribute to reducing organizations’ environmental impacts through the integration of environmental practices into daily routines. This study explored how a green climate at the organizational and co-worker level and supervisor support help predict employees’ voluntary green behaviours at work, particularly regarding waste separation. Organizational identification’s mediating role in these relationships was also examined. Cross-sectional, correlational research was conducted at a Portuguese higher education institution in which 164 employees responded to an online survey. The results reveal a significant positive association between workers’ perceptions of a green organizational climate and their reported pro-environmental behaviours, but organizational identification does not mediate the green climate–pro-environmental behaviours relationship. In addition, supervisor support’s effect on pro-environmental behaviours was only marginally significant. These findings underline the importance of organizational-level initiatives as a way to promote green behaviours at work, but a better understanding of the processes generating these relationships is still needed. The practical implications include the need for more investment in initiatives that focus on making environmental concerns part of organizations’ daily procedures and routines.